Pé diabético : etiologia e resistência a antimicrobianos de cepas isoladas de 141 pacientes atendidos no Centro Integrado de Diabetes e Hipertensão do Estado do Ceará - Motta Neto, Renato (2003)
One-hundred-forty-one diabetic patients exhibiting infected ulcers were treated aí the Diabetic Center of Ceará from 01/03/2001 to 30/11/2001 and were submitted to a microbiology study at the microbiology laboratory of the legal medicine department/Federal University of Ceará, Brazil. Of these, 98 (69.5%) patients showed infections of the type polymicrobial where the classification of wagner prevalent in the studies was the degree II, found in 44% of the patients. 298 bactéria were isolated showing the following distribution: 177 (59.4%) Gram- negative baciili; 85 (28.5%) Gram-positive cocci; and 36 (12.1%) stricts anaerobes of, which 10 (3.4%) belong to the group of Bacteroides fragilis and 9 (3%) to the species Peptostreptococcus. The group of Gram-negative baciili, 156 (52.4%) belongs to the Enterobacteriaceae family and only 21 (7%) belongs to the species Pseudomonas aeruginosas. The most frequent of the Enterobacteriaceae family were: Klebsiella pneumoniae (11.1%), Morganella morganii (10.4%) and Escherichia coli (8.1%). From this family, the following K. pneumoniae species (07 strains), E. coli (03 strains). Enterobacteriaceae were isolated from 83.7% of the patients and Staphylococcus aureus from 43.3%. It is worth noting that the isolation of Streptococcuspyogenes was seen in 7.8% of the patients. The strains of S. aiireus 07 (11.5%) introduced resistence to Oxacillin (strains ORSA). All the patients infected by strains ORSA were interned and/or treated with antimicrobial during the few rnonths prior to the study. As diabetes mellitus type 2 is na endemic disease giving rise to diabetic foot, complications are more frequent. Therefore, a routine needs to be created in the diabetes centres to identify etiological agenís, the causes of these infections.